Islamic Boarding School Management as a Basic Treasure of Internationalization Islamic Higher Education - Ehwanudin, Ehwanudin; Afifuddin, M.; Ulumudin, M. Ikhya; Arifah, Ni'matul; Aula, Minhatul (International Journal on Advanced Science, Education, and Religion, 2024)
Management is one of the key elements in managing institutions or institutions, including in the context of Islamic Higher Education institutions. In order to improve the quality of education and community service, Islamic higher education is currently faced with demands to move progressively towards internationalization. This process requires a shift from a university orientation that focuses on teaching (teaching university) to a university that focuses on research (research university). This shift has had a significant impact, including changes in institutional structures, mindsets, paradigms, and the strategies implemented. This study aims to discuss the management of Islamic boarding school treasures with their unique scientific traditions, as a paradigmatic basis for Islamic higher education towards international standard universities. The method used in this study is descriptive qualitative with a library research approach. Through philosophical and phenomenological analysis, this study reveals that the integration between the concept of Islamic higher education and Islamic boarding school management can be used as a pilot model and source of inspiration in the development of Islamic higher education to achieve this grand vision.